Sociodemographic and clinical characteristics, causal factors and evolution of a group of patients with chronic urticaria-angioedema - Silvares, Maria Regina Cavariani; Coelho, Kunie Iabuki Rabello; Dalben, Ivete; Lastória, Joel Carlos; Abbade, Luciana Patrícia Fernandes (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Chronic urticariaangioedema is a common, multiple-cause complaint. The aim was to investigate the sociodemographic and clinical characteristics, causal and aggravating factors and evolution of urticaria-angioedema. DESIGN AND SETTING: This was a descriptive prospective study carried out at the Dermatology outpatient clinic of Faculdade de Medicina de Botucatu, Universidade Estadual Paulista (Unesp). METHODS: A total of 125 patients with chronic urticaria-angioedema were evaluated to obtain sociodemographic data, anamnesis, dermatological and general clinical data and laboratory data, emphasizing causal and aggravating factors and complaint evolution. RESULTS: Chronic urticaria-angioedema occurred mainly in females (mean age: 35 years), but also in men (mean age: 32 years). White color and living in urban areas also predominated. There was no preferential time for symptoms to appear, and nighttime was the most commonly reported time for clinical worsening. Around half of the patients had urticaria associated with angioedema. There were no associated factors in most of the cases, and stress was the most commonly reported aggravating factor. The cause was ascertained in 37.6% of our cases. The mean duration of follow-up was 11.7 months. Around 60% of the patients evolved with the problem under control, 32% improved, 9% had no change in dermatological condition and only one patient worsened. CONCLUSIONS: Chronic urticaria-angioedema was more common among middle-aged women. It is a long-term disease, and its cause was explained in about one-third of the patients. Half of the patients presented disease control after treatment lasting an average of approximately one year.